2021
DOI: 10.1017/s0033291721002373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on mismatch negativity and P3a amplitude of initially psychostimulant-naïve, adult ADHD patients

Abstract: Background Deficient information processing in ADHD theoretically results in sensory overload and may underlie the symptoms of the disorder. Mismatch negativity (MMN) and P3a amplitude reflect an individual's detection and subsequent change in attention to stimulus change in their environment. Our primary aim was to explore MMN and P3a amplitude in adult ADHD patients and to examine the effects of methylphenidate (MPH) on these measures. Methods Forty initially psychostimulant-naïve, adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…First, considering the previous research in adults, our findings indicated that 7- to 11-year-old TD children have developed “adult-like” N2ac, suggesting that the ability of TD children to balance auditory selective attention and distractor suppression was similar to that of adults (Gamble and Luck, 2011 ; Gamble and Woldorff, 2015b ; Klatt et al, 2018 , 2020 ); meanwhile, the N2ac component of TD children, observed at the anterior contralateral electrode sites 200 to 350 ms after the stimulus onset in the N2 latency in our study, was consistent with previous studies in the lateral prefrontal cortex (LPFC), which suggested the association with the control of auditory attention (Bidet-Caulet et al, 2015 ). Second, considering previous debates on the auditory-related EEG components such as MMN or Nd in patients with ADHD (Satterfield et al, 1988 ; Jonkman et al, 1997 ; Rothenberger et al, 2000 ; Huttunen et al, 2007 ; Itagaki et al, 2011 ; Gomes et al, 2012 ; Cheng et al, 2016 ; Yamamuro et al, 2016 ; Rydkjær et al, 2017 ; Zhang et al, 2020 ; le Sommer et al, 2021 ), our findings provide the first evidence for the difference in the spatial auditory selective attention between children with ADHD and TD children, where the N2ac was absent in children with ADHD. Third, we found that the dysfunctional N2ac of children with ADHD was associated with higher inattentive symptom severity, such as the function of N2pc in visual attention (Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, considering the previous research in adults, our findings indicated that 7- to 11-year-old TD children have developed “adult-like” N2ac, suggesting that the ability of TD children to balance auditory selective attention and distractor suppression was similar to that of adults (Gamble and Luck, 2011 ; Gamble and Woldorff, 2015b ; Klatt et al, 2018 , 2020 ); meanwhile, the N2ac component of TD children, observed at the anterior contralateral electrode sites 200 to 350 ms after the stimulus onset in the N2 latency in our study, was consistent with previous studies in the lateral prefrontal cortex (LPFC), which suggested the association with the control of auditory attention (Bidet-Caulet et al, 2015 ). Second, considering previous debates on the auditory-related EEG components such as MMN or Nd in patients with ADHD (Satterfield et al, 1988 ; Jonkman et al, 1997 ; Rothenberger et al, 2000 ; Huttunen et al, 2007 ; Itagaki et al, 2011 ; Gomes et al, 2012 ; Cheng et al, 2016 ; Yamamuro et al, 2016 ; Rydkjær et al, 2017 ; Zhang et al, 2020 ; le Sommer et al, 2021 ), our findings provide the first evidence for the difference in the spatial auditory selective attention between children with ADHD and TD children, where the N2ac was absent in children with ADHD. Third, we found that the dysfunctional N2ac of children with ADHD was associated with higher inattentive symptom severity, such as the function of N2pc in visual attention (Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mismatch negativity (MMN) has typically been observed in various EEG studies with common auditory oddball or auditory Go/NoGo tasks, reflecting the automatic detection of unpredictable audio. The ADHD studies on MMN were extensive but controversial, reporting both reduced MMN amplitude in children with ADHD (Rothenberger et al, 2000 ; Cheng et al, 2016 ; Yamamuro et al, 2016 ; Zhang et al, 2020 ) and comparable MMN amplitudes in ADHD studies of children (Huttunen et al, 2007 ; Gomes et al, 2013 ), adolescents (Rydkjær et al, 2017 ), and adults (le Sommer et al, 2021 ), compared to the healthy controls. Meanwhile, it remains controversial whether and how the extent of selective attention is involved in MMN (Haroush et al, 2010 ; Fishman, 2014 ), especially regarding patients with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The robust difference between the study groups suggests, that aMMN can be a more reliable biomarker for monitoring drug effects and drug development, than vMMN. Mismatch negativity is still a promising candidate, since MMN impairment thought to be selective to schizophrenia 8 , 79 . Previous studies found reduced MMN in at-risk subjects converting to first psychosis but not in nonconverters and even in first degree relatives of schizophrenia patients 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Auditory MMN is impaired in bipolar disorder with psychotic features, but in a lesser extent, compared to schizophrenia. Patients with ADHD do not show significant MMN impairment, compared to healthy control subjects 8 . These findings indicate that MMN impairment tends to be somewhat specific to schizophrenia.…”
Section: Introductionmentioning
confidence: 92%